Glycoproteins of predicted amphibian and reptile lyssaviruses can mediate infection of mammalian and reptile cells - Oberhuber, Martina; Schopf, Anika; Hennrich, Alexandru Adrian; Santos-Mandujano, Rosalía; Huhn, Anna Gesine; Seitz, Stefan; Riedel, Christiane Maria; Conzelmann, Karl-Klaus (Viruses, 2021)
Lyssaviruses are neurotropic rhabdoviruses thought to be restricted to mammalian hosts, and to originate from bats. The identification of lyssavirus sequences from amphibians and reptiles by metatranscriptomics thus comes as a surprise and challenges the mammalian origin of lyssaviruses. The novel sequences of the proposed American tree frog lyssavirus (ATFLV) and anole lizard lyssavirus (ALLV) reveal substantial phylogenetic distances from each other and from bat lyssaviruses, with ATFLV being the most distant. As virus isolation has not been successful yet, we have here studied the functionality of the authentic ATFLV- and ALLV-encoded glycoproteins in the context of rabies virus pseudotype particles. Cryogenic electron microscopy uncovered the incorporation of the plasmid-encoded G proteins in viral envelopes. Infection experiments revealed the infectivity of ATFLV and ALLV G-coated RABV pp for a broad spectrum of cell lines from humans, bats, and reptiles, demonstrating membrane fusion activities. As presumed, ATFLV and ALLV G RABV pp escaped neutralization by human rabies immune sera. The present findings support the existence of contagious lyssaviruses in poikilothermic animals, and reveal a broad cell tropism in vitro, similar to that of the rabies virus.
Gesehen am 15.11.2021